Stomaching the pain of spinal fusion: Gastrointestinal discomfort is as severe as back pain in 50% of adolescent idiopathic scoliosis patients following posterior spinal fusion. (October 2018) - Villamor, G. A.; Andras, L. M.; Chan, P.; Jalloh, H.; Sanders, A. E.; Yang, J.; Choi, P. D.; Tolo, V. T.; Skaggs, D. L.
Abstract: Purpose: There have been no prospective studies investigating gastrointestinal (GI) symptoms of patients with adolescent idiopathic scoliosis (AIS) following posterior spinal fusion (PSF). The purpose of this study was to evaluate the incidence and severity of self-reported GI symptoms following PSF. Methods: In all, 40 AIS patients undergoing PSF were prospectively enrolled between March 2015 and October 2016. Patients completed a survey on each postoperative, inpatient day regarding nausea, emesis, constipation, abdominal pain and back pain, rating their pain on a scale of 1 to 10. Results: Abdominal pain (50%), emesis (63%), nausea (65%) and constipation (68%) were experienced by the majority of patients. Of those reporting back pain, the mean pain level during the postoperative period was 5.1 (0.2 to 9.6). Of those reporting abdominal pain, the mean pain level during the postoperative period was 5.5 (1.4 to 8.6), which was not different than the severity of their back-pain levels (mean = 6.0, p = 0.31). Conclusions: Gastrointestinal issues in AIS patients following PSF are common. Abdominal pain was as severe as the back pain for half of the patients. Level of Evidence: II